FORMATION OF MORAL NORMS IN PRESCHOOL CHILDREN THROUGH MUSICAL AND CREATIVE GAMES - Лісовська, Тетяна; Тесленко, Світлана (Modern engineering and innovative technologies, 2024)
The article deals with the problem of forming moral norms in preschool children through musical and creative games as an important component of the educational process. The moral development of children is one of the key tasks of preschool education, beca